Application status of royal jelly in the medical field - Huang, Jun-Hong; Wang, Qian-Qian; Zhang, Shi-Yi; Zhang, Chu-Yue; Huang, Yu; Feng, Yan-Xia; Feng, Shu-Ying (Journal of functional foods, 2025)
Royal jelly (RJ), a representative product of food-medicine homology, possesses complex bioactive components including major royal jelly proteins (MRJPs) and 10-hydroxy-2-decenoic acid (10-HDA), contributing to its multifaceted pharmacological functions. This review systematically summarizes RJ's compositional profile, analytical techniques, and therapeutic effects across organ protection, antioxidant, anti-inflammatory, anticancer, neuroprotective, and immunomodulatory domains. Clinical and preclinical studies highlight RJ's efficacy in managing metabolic disorders, reproductive dysfunction, neurodegenerative diseases, and promoting wound healing. Despite these findings, translation to clinical use remains limited by factors such as unclear mechanisms, low oral bioavailability, and the lack of high-quality randomized trials. Future research should prioritize standardization of RJ formulations, mechanistic elucidation of key components, pharmacokinetic profiling, and interdisciplinary integration, including nanotechnology and traditional medicine. These directions are critical to unlocking RJ's potential as both a functional food and biotherapeutic agent, promoting its role in modern health strategies rooted in food-medicine homology. [Display omitted] •Global market analysis indicates RJ sector growth, driven by demand for functional foods and biomaterials.•RJ contains unique bioactive compounds (10-HDA, MRJPs) absent in other bee products, with notable dietary value.•RJ’s antioxidant, anti-inflammatory, immunomodulatory, organ protective, and metabolic effects promote health.•Standardization and clinical validation are essential to advance RJ from nutraceuticals to therapeutic use.